Heavy metal content in coral reef-associated fish collected from the central Red Sea, Saudi Arabia - Al Solami Lafi (Oceanological and Hydrobiological Studies)
The concentration of heavy metals in marine fish is important for assessing the health risks associated with fish consumption. In this study, the concentration of metals such as copper, lead and manganese were analyzed in the muscle tissue of five coral reef-associated fish species collected from the central Red Sea, Saudi Arabia. The maximum copper content of 0.183 μg g-1 (ww) was detected in fish samples. Fish samples also showed maximum lead and manganese values of 0.030 and 0.064 μg g-1 (ww), respectively. The metal concentration in fish tissue samples did not vary significantly between the fish species. In conclusion, the results obtained indicate that the content of heavy metals in the coral reef-associated fishes is below the values determined by various agencies for seafood safety.